Contraction influences Per2 gene expression in skeletal muscle through a calcium‐dependent pathway - Small, Lewin (J Physiol, 2020)
KEY POINTS: Exercising at different times of day elicits different effects on exercise performance and metabolic health. However, the specific signals driving the observed time‐of‐day specific effects of exercise have not been fully identified. Exercise influences the skeletal muscle circadian clock, although the relative contribution of muscle contraction and extracellular signals is unknown. Here, we show that contraction acutely increases the expression of the core circadian clock gene Period Circadian Regulator 2 (Per2) and phase‐shifts Per2 rhythmicity in muscle cells. This contraction effect on core clock genes is mediated through a calcium‐dependant mechanism; The results obtained in the present study suggest that a proportion of the ability of exercise to entrain the skeletal muscle clock is driven directly by muscle contraction. Contraction interventions may be used to mimic some time‐of‐day specific effects of exercise on metabolism and muscle performance. ABSTRACT: Exercise entrains the central and peripheral circadian clocks, although the mechanism by which exercise modulates expression of skeletal muscle clock genes is unclear. The present study aimed to determine whether skeletal muscle contraction alone could directly influence circadian rhythmicity and uncover the underlying mechanism by which contraction modulates clock gene expression. We investigated the expression of core clock genes in human skeletal muscle after acute exercise, as well as following in vitro contraction in mouse soleus muscle and cultured C2C12 skeletal muscle myotubes. Additionally, we interrogated the molecular pathways by which skeletal muscle contraction could influence clock gene expression. Contraction acutely increased the expression of the core circadian clock gene Period Circadian Regulator 2 (Per2) and phase‐shifted Per2 rhythmicity in C2C12 myotubes in vitro. Further investigation revealed that pharmacologically increasing cytosolic calcium concentrations by ionomycin treatment mimicked the effect of contraction on Per2 expression. Similarly, treatment with a calcium channel blocker, nifedipine, blocked the effect of electric pulse stimulation‐induced contraction on Per2 expression. Increased calcium influx from contraction lead to binding of the phosphorylated form of cAMP response element‐binding protein (CREB) to the Per2 promoter, suggesting a role of CREB in contraction‐induced Per2 transcription. Thus, by dissociating the effect of muscle contraction alone from the whole effect of exercise, our investigations indicate that a proportion of the ability of exercise to entrain the skeletal muscle clock is driven directly by contraction.